What can we learn from offspring studies in bipolar disorder?. (May 2016) - Loftus, Josephine; Etain, Bruno; Scott, Jan
Summary: We offer a contemporary review of studies of the offspring of parents with bipolar disorder and explore the clinical characteristics of these populations. We discuss how different methodological approaches may influence study findings and may explain some of the heterogeneity in the results reported. We also highlight some of the environmental risk factors that may increase the likelihood of transition from an 'at-risk' or high-risk state to bipolar disorder. Last, we briefly discuss the implications of study findings for early intervention strategies and comment on such issues as genetic counselling and primary and early secondary prevention programmes.